Phytosociological analysis of ecological trail located in Mixed Ombrophilous Forest (Revista de Ciências Agroveterinárias, 2015)
The present study aimed to characterize the floristic composition and structure of the arborous vegetation along an ecological trail, located at a Rural Hostel, in Lages, SC, in order to verify how representative it is of the regional Araucaria Forest and to infer its potential as a tool for environmental education. The sampling was conducted by using the quadrant point method along an ecological trail through 100 points, 10 m apart from each other, where 400 individual trees, with circumference at chest height (at 1.30 m) greater than or equal to 15 cm were measured and identifi ed. The Shannon diversity index, Pielou equability and classical phytosociological descriptors were determined. The representativeness of the ecological trail was inferred through comparison between the observed results and the published scientific literature containing structural and floristic descriptions of the regional forest fragments. A total of 44 species, 38 genera and 25 families were identified, with Myrtaceae as the richest family. The diversity was 2.98 nats ind.-1, and the equability was 0.79. Araucaria angustifolia, Calyptranthes concinna and Dicksonia sellowiana were the species with the highest importance values. Considering the regional context, the results suggest that the ecological trail appropriately represents the forest fragments in the region, indicating its high potential to be used as a tool for environmental education.
Keywords: Araucaria forest; Environmental education; Tree species.